2008
DOI: 10.1055/s-0028-1084474
|View full text |Cite
|
Sign up to set email alerts
|

Non-cannabinoid constituents from a high potency Cannabis sativa variety

Abstract: Six new non-cannabinoid constituents were isolated from a high potency Cannabis sativa L.variety, namely 5-acetoxy-6-geranyl-3-n-pentyl-1,4-benzoquinone (1), 4,5-dihydroxy-2,3,6-trimethoxy-9,10-dihydrophenanthrene (2), 4-hydroxy-2,3,6,7-tetramethoxy-9,10-dihydrophenanthrene (3), 4,7-dimethoxy-1,2,5-trihydroxyphenanthrene (4), cannflavin C (5) and β-sitosteryl-3-O-β-D-glucopyranoside-2'-O-palmitate (6). In addition, five known compounds, α-cannabispiranol (7), chrysoeriol (8), 6-prenylapigenin (9), cannflavin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Antileishmanial activity for cannflavin B (the double bond between C-2 and C-3, C-6 prenyl, 5 mM) has also been observed (Radwan et al 2008b). Radwan et al (2008a) also reported a moderate activity of cannflavin A (17 mg/mL, 39 mM). Salem et al (2011) have published some data about the antileishmanial activity of the C-geranyl flavonoids that are in good agreement with the data presented here.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Antileishmanial activity for cannflavin B (the double bond between C-2 and C-3, C-6 prenyl, 5 mM) has also been observed (Radwan et al 2008b). Radwan et al (2008a) also reported a moderate activity of cannflavin A (17 mg/mL, 39 mM). Salem et al (2011) have published some data about the antileishmanial activity of the C-geranyl flavonoids that are in good agreement with the data presented here.…”
Section: Resultsmentioning
confidence: 91%
“…The activity of 3 0 -O-methyl substituted dihydroflavonol 3 was diminished probably due to the presence of 3-OH substitution. C-6-Substituted compounds isolated from C. sativa such as cannflavin C are structurally very similar to compound 4 (except for the double bond between C-2 and C-3), and they have been reported to show an IC 50 value of 4.5 mg/mL (cannflavin C, close to 10 mM) against L. donovani (Radwan et al 2008a). Antileishmanial activity for cannflavin B (the double bond between C-2 and C-3, C-6 prenyl, 5 mM) has also been observed (Radwan et al 2008b).…”
Section: Resultsmentioning
confidence: 99%
“…18 More than 500 constituents have been identified in C. sativa. [18][19][20][21][22][23] C21 terpenophenolic cannabinoids are the most common and extensively studied class of cannabis constituents. The term cannabinoids represents a group of compounds found distinctively in C. sativa.…”
Section: Phytochemistrymentioning
confidence: 99%
“…25 The number of natural compounds identified in C. sativa is continuously increasing; for example, there were 423 in 1980, 26 483 in 1995 23 and more than 525 in 2008. [18][19][20][21][22][23] Described below is a brief overview of the phytochemical aspects of C. sativa, with special focus on the psychoactive components (e.g., cannabinoids).…”
Section: Phytochemistrymentioning
confidence: 99%
“…These two compounds occur in high amounts in most cannabis strains, either with a predominance of one over the other or with relatively equal amounts. This relative amount allows a differentiation between two main groups, one mostly diagnosed as "high in THC", which are related to sativa-originated strains and the other, "high in CBD" that are more indica-related strains [26]. However, over the last decade, many more phytocannabinoids were identified and their structure was more thoroughly studied [2,[26][27][28].…”
mentioning
confidence: 99%